Efficiency Analysis of Financing Companies Listed on the Indonesia Stock Exchange (IDX) During Covid-19 - Jalaludin, Engga; Sari, Maya (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
Economic shocks that occur during Covid-19 are also a risk for finance companies. The purpose of this study is to analyze efficiency as an indicator of the performance of finance companies. Company performance will be stable if it is able to allocate resources to produce maximum output. The Data Envelopment Analysis (DEA) method as a non-parametric approach is used to measure company efficiency during the 2020-2022 period. The research was conducted on 7 go public finance companies, data obtained from financial statements. Measurement of input variables, namely Assets, Equity, Operating Expenses. Output variables are net income and ROE. The results showed the efficiency value experienced a significant increase in line with economic recovery during Covid-19 in Indonesia. The lowest average efficiency was obtained in 2020, the first time Covid-19 was present in Indonesia at 70.52%, in 2021 at 76.59%, and in 2022 at 84.30%. Companies that consistently obtain 100% efficiency are Buana Finance Tbk and Wahana Ottomitra Multiartha Tbk. The result shows that the DEA projection value is lower than the actual data of the company. Company policy is needed to evaluate the use of inputs.